EFEKTIVITAS MEDIA VIDEO SINEMATIK DALAM MENGEMBANGKAN PEMAHAMAN BULLYING PADA SISWA SMP KELAS VII - Kustiana, Diki; Supriatna, Ecep; Masyita Suherman, Maya (IKIP Siliwangi, 2024)
The background of this research is the prevalence of bullying behavior in the school environment so that there is a need for education or understanding of the negative impacts of bullying behavior. The purpose of this study was to see the effectiveness of group guidance through cinematic video media to provide an understanding of bullying behavior towards students. This study is a pre-experimental design research using a one group pretest-posttest design because this design is designed to compare a treatment. This study uses a quantitative approach. The subjects in this study were students of SMP Plus Darul Amanah Ciwidey, totaling 30 students. The analysis of this research uses the Paired Sample T-Test formula. Based on the results of the research, it shows that group guidance using cinematic video can improve the ability to understand bullying behavior which can be seen from the significant difference from the average before group guidance of 81 and after career guidance of 116. The conclusion in this study is that group guidance using cinematic video media can improve the understanding of bullying behavior for grade VII students of SMP Plus Darul Amanah Ciwidey.